Review of Regulatory Challenges in Digital Platforms: Cases from India - Asrani, Chavi (International Journal of Psychosocial Rehabilitation, 2020)
Information Communications Technology (ICT) networks and infrastructure are now critical resources for organizations to run their business, compete and contribute productively in the new age digital markets. ICT has supported novel commercial models (Internet firms), 'digital platforms', by redefining delivery of goods and services and has significantly enhanced consumer welfare. The presence of intrinsic network effects in case digital platforms combined with the limited interoperability makes the prevalent digital ecosystem to have monopolistic structure or at best an oligopolistic market structure. There are regular entry and exit in digital markets, firms exercise mergers and acquisitions as a business strategy to establish its market share or diversify into new business areas. The power of user information (through data) enables the firms to practice price discrimination, thereby appropriating consumer surplus. Thus, competition issues in the new age digital markets must to be tackled by the competition authority taking cognizance that the regulatory regime does not curb the motivation to innovate. The paper reviews the competition issues i n digital ecosystem from the Indian perspective and reflects possible solutions to safeguard competition in the digital markets.